Sociobiology of communication an interdisciplinary perspective - d'Ettorre, Patrizia; Hughes, David P. (Oxford : Oxford University Press, 2008)
This text fills the gap between a proximate and ultimate level of analysis of social behaviour. It provides a unifying and synthetic view to identify the fundamental principles of communication across a broad range of model systems and taxa.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social interaction; Sociobiology; Interpersonal communication